2020
DOI: 10.1002/adfm.201910765
|View full text |Cite
|
Sign up to set email alerts
|

Removing the Obstacle of Dye‐Sensitized Upconversion Luminescence in Aqueous Phase to Achieve High‐Contrast Deep Imaging In Vivo

Abstract: Although upconversion nanoparticles (UCNPs) have drawn increasing attention for their unique photophysical characteristics, they suffer from a bottleneck of low luminescence efficiency due to the poor absorption coefficient of Ln 3+ . Dye sensitization has provided thousands-fold enhancement of upconversion luminescence (UCL) in organic solvents because of the remarkably improved light absorption ability, but the sensitization of UCL in aqueous phase is only less than 20 folds by far, with unknown restrictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 47 publications
0
55
0
Order By: Relevance
“…[7,15,17,41,46,[50][51][52]60,61] In vivo toxicity of NIR dye/LnNP nanoprobes has also been evaluated by hematology analysis, blood biochemical assay, and histological analysis on 7 or 15 days after intravenous injection of the nanoprobes into the nude mice. [54,[62][63][64] All the results showed no inflammatory response, nor any tissue injury in the treated mice as compared to the control group. In contrast, Pb/Cd-based QDs probes have Pb 2+ /Cd 2+ -induced cytotoxic effect and influence the hematopoiesis through oxidative stress.…”
Section: Biocompatibility Of Nanoprobesmentioning
confidence: 82%
See 2 more Smart Citations
“…[7,15,17,41,46,[50][51][52]60,61] In vivo toxicity of NIR dye/LnNP nanoprobes has also been evaluated by hematology analysis, blood biochemical assay, and histological analysis on 7 or 15 days after intravenous injection of the nanoprobes into the nude mice. [54,[62][63][64] All the results showed no inflammatory response, nor any tissue injury in the treated mice as compared to the control group. In contrast, Pb/Cd-based QDs probes have Pb 2+ /Cd 2+ -induced cytotoxic effect and influence the hematopoiesis through oxidative stress.…”
Section: Biocompatibility Of Nanoprobesmentioning
confidence: 82%
“…ACQ effect of NIR dyes on the surface of LnNP is the most important factor limiting the sensitization efficiency. [54] In NIR dye/LnNP nanocomposites, the amount of NIR dye should be optimized to enhance the overall absorption with enough dyes and avoid the undesired self-quenching. Encapsulation by an amphiphilic polymer can provide a local hydropho-bic environment in aqueous solution, which is often used to reduce the degree of dye aggregation and increase the optimal concentration of NIR dye in the system.…”
Section: Aggregation Of Nir Dyementioning
confidence: 99%
See 1 more Smart Citation
“…During the coordination of dyes with UCNPs, a high percentage of aggregated dyes are yielded on the nanoparticle surface owing to the aromatic p-conjugation plane and electrically charged head groups of cyanine dyes. [29][30][31][32] In particular, H-aggregation is high undesirable, resulting in strong fluorescence quenching effect to reduce the optimum number of dyes on the UCNP surface. Liu et al revealed that the aggregationcaused quenching of dyes is the most important reason limiting dye-sensitized upconversion.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the potential to achieve efficient solar energy utilization and good redox effects by combining UPT and photocatalytic materials, [29][30][31][32][33][34] in this study, Y 2 O 3 was co-doped with Tm 3+ and Yb 3+ to form an activator-sensitizer system (Y 2 O 3 :Yb 3+ , Tm 3+ ) using a sol-gel method. The effect of the Tm 3+ and Yb 3+ doping amount on the photoconversion performance of the UCNPs was then analyzed, and the photoconversion mechanism was evaluated.…”
Section: Introductionmentioning
confidence: 99%